Quantitative Analysis Of Medical Records In Typhoid Patients At Madani General Hospital Medan - Ritonga, Zulham Andi; Hasibuan, Ali Sabela; Siringoringo, Monika Belawanti (SEAN Institute, 2023)
Completeness of filling out medical records in hospitals is a requirement for quality medical records and can be done with quantitative analysis. The purpose of the study was to determine the quantitative analysis of medical records in Typhoid patients at Madani General Hospital. This study used descriptive research with a quantitative approach. The study was conducted at Madani General Hospital Medan. The study population was 1,237 and samples were obtained as many as 92 medical records. The results of the study reviewed item identification of patient names 88 medical records (96%) complete, medical record numbers 88 medical records (96%) complete, date of birth 85 medical records (92%) complete and gender 82 medical records (89%) complete. Review of important reporting on integrated initial review items 83 medical records (90%) complete, general consent 78 medical records (85%) complete, admission & exit summary 84 medical records (91%) complete, integrated patient progress records 86 medical records (93%) complete, medical resume 80 medical records (87%) complete and patient discharge plan 81 medical records (88%) complete. Review of auntetification on doctor name items 50 medical records (54%) complete, doctor's signature 55 medical records (60%) complete, nurse name 58 medical records (63%) complete, nurse signature 64 medical records (70%) complete, and professional degree 50 medical records (54%) complete. Review of correct documentation on items clearly reads 88 medical records (96%) complete, abbreviation use 89 medical records (97%) complete, error correction 64 medical records (70%) complete and blanks 85 medical records (92%) complete. It is recommended that the Madani Medan General Hospital re-socialize and provide training related to filling out medical records.